Do sonographic and cytological features predict malignancy in cytologically indeterminate thyroid nodules? - Dutta, S (The Royal College of Surgeons of England, 2011)
INTRODUCTION: The current algorithm for managing patients with indeterminate (Thy3) thyroid cytology is a thyroid lobectomy followed by a completion thyroidectomy depending on histology. We investigated whether sonographic and or cytological features in addition to clinical characteristics would predict the potential for malignancy in a cohort of patients with thyroid nodules of indeterminate cytology. METHODS: Perusing a clinical database of all patients undergoing ultrasonography guided fine needle aspiration (FNA) of thyroid nodules, we identified all Thy3 lesions. The demographic, ultrasonography and cytological details of benign and malignant groups were compared by t-test, chi-square test and, when appropriate, Fisher's exact test. Association between studied characteristics and malignancy was tested by binary logistic regression using single input. A p-value of <0.05 was considered significant. RESULTS: During the retrospective study period of January 2003 to July 2010, a total of 1,019 patients underwent FNA, of which 69 (6.8%) were classed as Thy3. Of these, 59 underwent surgical treatment and the histological outcomes were grouped as benign (n=42, 71.2%) and malignant (n=17, 28.8%). These groups were analysed for the predictive variables. Age, sex and sonological characters were similar in the two groups (p>0.05). The two microcalcifications observed were both in the malignant group. Among all the variables assessed, only the absence of normal follicular cells was associated with malignant nodules (univariate analysis, p=0.034). CONCLUSIONS: Malignancy was more common in Thy3 patients with an absence of normal follicular cells and such patients may therefore warrant a total thyroidectomy.